2010
DOI: 10.3174/ajnr.a2226
|View full text |Cite
|
Sign up to set email alerts
|

Natalizumab (Tysabri)

Abstract: SUMMARY: Natalizumab is a humanized IgG4 monoclonal antibody that is a selective adhesion molecule inhibitor, which prevents adhesion of leukocytes to endothelial cells. It is the first monoclonal antibody approved by the FDA for the treatment of relapsing-remitting MS. This article will review the mechanism of action and clinical role of this agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 17 publications
1
35
0
3
Order By: Relevance
“…The reduction in λ ⊥ may be indicative of remyelination. Natalizumab is an anti-inflammatory drug that prevents leukocyte adhesion to the capillary endothelial cells and, as a result, reduces leukocytes entering the CNS [57]. Natalizumab therapy has been shown to reduce conversion of gadolinium-enhancing lesions into T1 black holes, which are indicative of severe tissue damage comprising axonal loss, axonal swelling and demyelination [58].…”
Section: Cns Demyelination: Msmentioning
confidence: 99%
“…The reduction in λ ⊥ may be indicative of remyelination. Natalizumab is an anti-inflammatory drug that prevents leukocyte adhesion to the capillary endothelial cells and, as a result, reduces leukocytes entering the CNS [57]. Natalizumab therapy has been shown to reduce conversion of gadolinium-enhancing lesions into T1 black holes, which are indicative of severe tissue damage comprising axonal loss, axonal swelling and demyelination [58].…”
Section: Cns Demyelination: Msmentioning
confidence: 99%
“…In particular, it binds to alpha-4-beta-1 integrin, blocking the interaction with its analog receptor, the vascular cell adhesion molecule-1 (VCAM-1). Disruption of these molecular interactions prevents mononuclear leukocyte migration across the endothelium into the inflamed parenchymal tissue (Selewski et al, 2010). In a recent study analyzing plasma PEVs, LEVs, and MEVs, our group found higher counts of all three EV subtypes in IFN-beta and natalizumab-treated than untreated patients (Sáenz-Cuesta et al, 2014).…”
Section: Are Evs Reliable Biomarkers In Ms?mentioning
confidence: 99%
“…Although it has been shown to inhibit T cell activation and promote anti‐inflammatory responses, this treatment is associated with severe flu‐like symptoms, which can lead to suboptimal patient compliance . Another protein based therapy, Natalizumab (Tysabri) is an antibody that diminishes the inflammatory responses and suppresses the demyelination process . Natalizumab binds to α4‐integrin on leukocytes, which blocks their interaction with endothelial cells via vascular cell adhesion molecule‐1 (VCAM‐1), and inhibits their migration across the blood–brain barrier.…”
Section: Introductionmentioning
confidence: 99%